Efficacy of noninvasive brain stimulation techniques in managing stuttering behaviors: a systematic review and meta-regression analysis - Rasoli Jokar, Amir Hossein; Bayat, Behnaz; Ghadami, Ali; Dehkordi, Morteza Soleyman (Journal of speech, language, and hearing research, 2025)
Purpose: - This systematic review and meta-regression analysis investigated the overall effectiveness of noninvasive brain stimulation (NIBS) techniques in managing stuttering behaviors. - Method: - A total of 290 papers were initially identified through a comprehensive database search, and after applying inclusion and exclusion criteria, 15 studies were selected for the final analysis. These studies evaluated NIBS techniques both as standalone interventions and in combination with speech therapy techniques. The random-effects meta-analysis was done to investigate the effect of neuromodulation techniques on reducing severity and frequency of stuttering behaviors. In addition, meta-regression and subgroup analyses were conducted to identify the effective techniques and explore potential moderators, such as intervention type, age group, and outcome measures. - Results: - The random-effects meta-analysis revealed a significant positive effect of neuromodulation techniques on reducing stuttering severity and frequency. Meta-regression showed that transcranial direct current stimulation (tDCS) had the most significant effect in reducing stuttering severity and frequency among standalone interventions. Combined therapy approaches, which paired NIBS with speech therapy, resulted in the most substantial improvements overall. Sensitivity analyses confirmed the robustness of the results despite minor heterogeneity across studies. - Conclusions: - NIBS, particularly tDCS, shows promise as an effective intervention for stuttering. When combined with behavioral therapies, NIBS offers enhanced benefits, supporting its role as an adjunctive treatment in clinical practice. Further large-scale studies are recommended to confirm the long-term efficacy, refine treatment protocols, and explore optimal stimulation parameters for improved outcomes.